2005
DOI: 10.1063/1.1870098
|View full text |Cite
|
Sign up to set email alerts
|

Polarization fatigue in PbZr0.45Ti0.55O3-based capacitors studied from high resolution synchrotron x-ray diffraction

Abstract: High resolution synchrotron x-ray diffraction experiments were performed on (111)-oriented PbZr0.45Ti0.55O3-based capacitors with a composition in the morphotropic region. Diffraction analyzes were done after bipolar pulses were applied and removed, representing several places in the cyclic switching. Microstructural changes were evidenced from relative diffracted intensities variations of several Bragg reflections and a correlation with the evolution of the ferroelectric responses has been established. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…Wake-up studies on PZT material system were performed and reported before. [15,29,30] On the other hand, a very detailed and systematic review of fatigue mechanisms was reported by Tagantsev et al in 2001 [17] and Lou et al in 2009. [31] These studies suggested that a combination of several mechanisms (domain de-/ pinning, [32] seed inhibition, [33] and formation of the passive/ dead layer [34] ) could be responsible for the device wake-up and fatigue.…”
Section: Mechanismsmentioning
confidence: 93%
See 2 more Smart Citations
“…Wake-up studies on PZT material system were performed and reported before. [15,29,30] On the other hand, a very detailed and systematic review of fatigue mechanisms was reported by Tagantsev et al in 2001 [17] and Lou et al in 2009. [31] These studies suggested that a combination of several mechanisms (domain de-/ pinning, [32] seed inhibition, [33] and formation of the passive/ dead layer [34] ) could be responsible for the device wake-up and fatigue.…”
Section: Mechanismsmentioning
confidence: 93%
“…The initial increase in the MW observed up to 10 3 cycles correlates with the "wake-up" effect as reported elsewhere. [15,16,20] With further field cycling, the continuous switching of the polarization state reduces the MW.…”
Section: Built-in Bias Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional peaks for BiFeO 3 indicate that new ferroelastic domains formed during fatigue cycles and that fatigued (111) pc BiFeO 3 films have four ferroelastic variances. Previously, there were reports on fatigue characteristics of rhombohedral ferroelectrics: ferroelastic domain evolution with polarization fatigue in textured films [43,44] and ceramics [45,46] of PZN-PT, which are initially multi-domain states. However, these new ferroelastic domains are nucleated from the initial monodomain state with fatigue in our work.…”
Section: Polarization Fatigue: Reliability With Cyclesmentioning
confidence: 99%
“…Domain switching was calculated from changes in integral intensities and lattice changes from peak shifts. 15,[19][20][21][22][23][24][25][26] Besides the work of Menou et al, 21 all these studies focused on donor doped material. For compositions close to the MPB mostly the model of a coexistence of a tetragonal and rhombohedral phase 26 or a tetragonal and monoclinic phase 23 was assumed and analyzes concentrated on the measurement of the pseudocubic ͕111͖ c and ͕200͖ c reflections assuming constant phase contents.…”
Section: 15mentioning
confidence: 99%